2018
DOI: 10.1371/journal.pone.0202624
|View full text |Cite
|
Sign up to set email alerts
|

Impact of asthma on women and men: Comparison with the general population using the EQ-5D-5L questionnaire

Abstract: BackgroundThe aim was to evaluate the impact of asthma on patients’ Health-Related Quality of Life (HRQoL) by comparing asthmatic women and men with reference norms, to examine the factors which contributed to an impaired HRQoL, and to identify groups at higher risk.MethodsCross-sectional evaluation of 222 primary care patients with persistent asthma (18–40 years old). HRQoL impact was estimated with the EuroQol-5 Dimensions (EQ-5D), which allows calculating Quality-Adjusted Life-Years (QALYs) by applying soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
3
16
0
1
Order By: Relevance
“…Although there is no previous evidence indicating the relationship between ACQ and vitamin D levels, a positive correlation between vitamin D levels and ACT was reported in asthmatic adults and children with moderate to severe asthma. 16,17) We found that the ACT and ACQ scores correlated with the EQ-5D index value, VAS, and PCS, in agreement with previous studies. 18,19) The difference in the association between ACT and ACQ may help explain the role of vitamin D in disease control and HR-QOL in patients with asthma.…”
Section: Discussionsupporting
confidence: 91%
“…Although there is no previous evidence indicating the relationship between ACQ and vitamin D levels, a positive correlation between vitamin D levels and ACT was reported in asthmatic adults and children with moderate to severe asthma. 16,17) We found that the ACT and ACQ scores correlated with the EQ-5D index value, VAS, and PCS, in agreement with previous studies. 18,19) The difference in the association between ACT and ACQ may help explain the role of vitamin D in disease control and HR-QOL in patients with asthma.…”
Section: Discussionsupporting
confidence: 91%
“…According to the result of this study patients those who uses health insurance were correlated signi cantly with HRQoL. This positive association between health insurance and HRQoL were supported by other studies [12,24,25,[39][40][41][42][43][44]. The possible explanation for this positive association might be mainly to high levels of adherence, reduce out pocket cost for drug and use of treatment as per guidelines increased in health insured participants.…”
Section: Discussionsupporting
confidence: 83%
“…Encontramos estudios en los que se analizó la CVRS en relación con el buen manejo de la patología crónica en los que desapareció esa diferencia asociada con el género, siendo dependiente de un mejor control en la enfermedad. El estudio realizado por Hernández identificó la gravedad y el control de síntomas del asma como el principal contribuyente a la alteración de la CVRS, independientemente de su sexo, sugiere que el impacto del asma en la CVRS podría aliviarse logrando un buen control de los síntomas 22 . Otros estudios realizados con pacientes con EPOC o DM, también atribuyeron una peor calidad de vida cuando la gravedad de la patología es mayor y el control de los síntomas peor 23 , 24 .…”
Section: Discussionunclassified